2018
DOI: 10.1177/1074248418769638
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolism and Mortality in the Tasmanian Atrial Fibrillation Study

Abstract: Thromboembolic event and all-cause mortality rates were lower following the widespread availability of DOACs in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In patients with atrial fibrillation, oral anticoagulation reduces the risks of ischemic stroke and systemic embolism in patients with atrial fibrillation by 60–70% [6]. In comparison to VKA, a retrospective study showed that the overall thrombosis rate and transient ischemic attack (TIA) rate after taking DOACs were 1.7 per 100 person-years and 1.3 per 100 person-years, respectively, significantly lower than the 3.2 per 100 person-years and 2.1 per 100 person-years in the VKA group, but there was still a risk of thromboembolism [7]. Therefore, a scoring system that can reliably predict the risk of DOAC-induced thromboembolism is an essential tool for the clinician.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with atrial fibrillation, oral anticoagulation reduces the risks of ischemic stroke and systemic embolism in patients with atrial fibrillation by 60–70% [6]. In comparison to VKA, a retrospective study showed that the overall thrombosis rate and transient ischemic attack (TIA) rate after taking DOACs were 1.7 per 100 person-years and 1.3 per 100 person-years, respectively, significantly lower than the 3.2 per 100 person-years and 2.1 per 100 person-years in the VKA group, but there was still a risk of thromboembolism [7]. Therefore, a scoring system that can reliably predict the risk of DOAC-induced thromboembolism is an essential tool for the clinician.…”
Section: Introductionmentioning
confidence: 99%
“…Atrial fibrillation (AF) is associated with significant morbidity, mortality and increased healthcare costs 1,2 . AF‐associated morbidity and mortality are mainly due to thromboembolic 3 and other cardiovascular complications, such as stroke, myocardial infarction (MI), ischaemic heart disease, heart failure and cardiac arrest 4–7 . Stroke associated with AF is usually more severe and fatal than stroke of other aetiologic origins, but is largely preventable with oral anticoagulation 3 .…”
Section: Introductionmentioning
confidence: 99%